Eveloping self-facilitating learning networks for entrepreneurs: a guide to action. (1st January 2014) - Power, John; Sinnott, Eileen; O'Gorman, Bill; Fuller-Love, Nerys
A longitudinal study conducted over a three-year period established six learning networks consisting of 105 entrepreneurs and SME owner/managers. The principal objective of the study was to uncover the critical elements that ensure networks operate effectively in order to advise and inform on practice for the creation of sustainable self-facilitated learning networks. The methodological approach adopted for this study was primarily direct participant observation. Findings provide a guide to action for the development of self-facilitated sustainable learning networks. This paper makes a significant contribution to practice providing knowledge on how to create sustainable learning networks thus having implications for entrepreneurs, government, policy-makers and academics interested in understanding how to effectively guide the development of sustainable learning networks for entrepreneurs to solve their own problems. This paper concludes with a discussion of theoretical and applied significance.